Memahami Kisah-Kisah Dalam Al-Qur’an - Hakmi Hidayat; Alvin Nurafrizal; Sri Ramadani; Diva Alawiyah Batubara (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
The stories in the Al-Quran are great literary works that have certain goals and themes, and function to provide wisdom and inspiration for their readers. These stories are not told sequentially and at length, but are often repeated with certain characteristics. The purpose of the stories in the Koran is to convey the truth, direct religious aspects, and provide inspiration so that people can improve their lives. The Koran is a guide to life for Muslims and contains stories and history that are worth emulating. The stories in the Qur’an are divided into three types, namely stories of the prophets, stories of previous people, and stories of the Prophet’s time. The stories in the Qur'an have different characteristics from the stories created by humans. The article discusses various points of view of Al-Quran stories and their relevance in moral education, including methods of understanding Al-Quran stories, the importance of stories in Al-Quran education, and the values ​​contained in Al-Quran stories. Sayyid Qutb’s work on fine art in the Koran is also one of the references in this article. The data analysis method used is inductive and comparative. From this analysis, the article concludes that the stories in the Koran have high moral and pedagogical value and can be a guide for Muslims in everyday life. or interpretations. The abstract should be an objective representation of the article and it must not contain results that are not presented and substantiated in the main text and should not exaggerate the main conclusions.